2009
DOI: 10.1142/s0217979209063390
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Band Gap Formation in Two-Dimensional Locally Resonant Sonic Crystals Comprised of Helmholtz Resonators

Abstract: We present a new type of sonic crystal technology offering a novel method of achieving broad acoustic band gaps. The proposed design of a locally resonating sonic crystal (LRSC) is constructed from "C"-shaped Helmholtz resonators as opposed to traditional solid scattering units. This unique construction enables a two band gap system to be generated in which the first — a Bragg type band gap, arises due to the periodic nature of the crystal, whilst the second gap results from resonance of the air column within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…The proposed systems have been studied numerically with the use of finite elements methods (FEM). So far the results are in complete agreement with laboratory experiments, see also Refs [4].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The proposed systems have been studied numerically with the use of finite elements methods (FEM). So far the results are in complete agreement with laboratory experiments, see also Refs [4].…”
supporting
confidence: 88%
“…The proposed sonic crystal forms broad attenuation bands in the lower frequency regime and comprises concentric slotted cylinders. The preliminary results of this work is presented in Refs [4]. Previously Hu et al [5] constructed a sonic crystal lens composed of an array of two-dimensional Helmholtz resonators, which in the longwave regime was found to have a high relative acoustic refractive index n and at the same time, a small acoustic impedance Z mismatch with air for airborne sound.…”
mentioning
confidence: 91%
“…With respect to the BEM, Duhamel [23] extended the two-dimensional modeling approach by incoherent line sources and refers to it as 2.5-dimensional boundary element method. In contrast, Chalmers et al [24] and Elford et al [8] assumed that the height of the sonic crystals is infinite and that ground effects are negligible. This allows to modify the cross section of the sound barrier along its length.…”
Section: Introductionmentioning
confidence: 99%
“…Devices based on HRs have been studied theoretically and experimentally over the last decade [19][20][21]. The periodic properties of 2D phononic crystals and HRs have also been discussed extensively; it has been proposed that these types of structures contained acoustic band gaps and that these band gaps could prevent sound waves from specific frequency regions from propagating inside the structures [22][23][24][25][26]. It was also indicated that the type of band gap that occurs in HR arrays was decoupled from the Bragg gaps [24].…”
Section: Introductionmentioning
confidence: 99%
“…When we compared the structures used in the literature [24][25][26] with our proposed structure, we found that the HR structures in the literature were arranged in a square lattice. However, this type of arrangement should consider the influences of both HR (local resonance) and the square lattice structure (Bragg's law).…”
Section: Introductionmentioning
confidence: 99%